2012
DOI: 10.1371/journal.pone.0053010
|View full text |Cite
|
Sign up to set email alerts
|

Human Sensory Neurons Derived from Induced Pluripotent Stem Cells Support Varicella-Zoster Virus Infection

Abstract: After primary infection, varicella-zoster virus (VZV) establishes latency in neurons of the dorsal root and trigeminal ganglia. Many questions concerning the mechanism of VZV pathogenesis remain unanswered, due in part to the strict host tropism and inconsistent availability of human tissue obtained from autopsies and abortions. The recent development of induced pluripotent stem (iPS) cells provides great potential for the study of many diseases. We previously generated human iPS cells from skin fibroblasts by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 60 publications
(65 reference statements)
1
58
0
Order By: Relevance
“…In addition, human neurons derived from induced pluripotent stem cells (iPSCs) (29), neuronal stem cells (30), and embryonic stem cells (ESCs) (31,32) have been explored as infection models for human alphaherpesvirus. While these human cells support HSV productive infection (24,(27)(28)(29)31), reliable models to study the establishment of latency and/or reactivation have not been achieved using these human cells.…”
mentioning
confidence: 99%
“…In addition, human neurons derived from induced pluripotent stem cells (iPSCs) (29), neuronal stem cells (30), and embryonic stem cells (ESCs) (31,32) have been explored as infection models for human alphaherpesvirus. While these human cells support HSV productive infection (24,(27)(28)(29)31), reliable models to study the establishment of latency and/or reactivation have not been achieved using these human cells.…”
mentioning
confidence: 99%
“…The infection of the HFF by a suspension of neurons that had been infected with cell free-VZV strongly suggests that these neurons produced VZV that readily infect susceptible cells. It has been shown by ourselves and others that cultured neurons infected with cell-associated VZV release virions into the medium (Gowrishankar et al, 2007), (Markus et al, 2011), (Lee et al, 2012). In a second approach, we tested the ability of hESC-derived neurons infected by cell-free VZV to not only produce but release infectious virions.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that cell-free VZV produced in a different laboratory (in China) has also recently been shown to generate productive infection (as shown by spread of infection, for example) of hESC-derived neurons and neuroblastoma-derived neurons (Selariu et al, 2012). Even more recently, incubation of human iPS-derived neurons with cell-free VZV was shown to result in release of infectious virus into the medium in (Lee et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The recent development of induced pluripotent stem cell (iPSC) and embryonic stem cell (ESC)-derived cells could theoretically enable this improved approach as multiple groups have shown that CNS derivatives can be derived from these cell populations [20,21]. One can envision using iPSCderived cells to make these disease models both cell-type and patient-specific lines so that the models express the cellular responses while also incorporating the patient's unique genetic profile.…”
Section: Modeling Disease Using Human Cells In General and Psc-derivementioning
confidence: 99%